Perception and Attitude of Emergency Room Resident Physicians toward Middle East Respiratory Syndrome Outbreak - Mohammed Al Ghobain; Turki Aldrees; Abdullah Alenezi; Saleh Alqaryan; Dana Aldabeeb; Najed Alotaibi; Abdulrahman Aldhabib; Shaker Alghalibi; Sami Alharethy (Emergency Medicine International)
Introduction. Middle East respiratory syndrome (MERS) outbreaks have had a considerable negative impact on health systems in Saudi Arabia. We aimed to study the psychological impact of a Middle East respiratory syndrome coronavirus (MERS-CoV) outbreak on emergency room resident physicians (ERRPs). Methods. We assessed the MERS-related psychological impact and concerns of ERRPs using a self-report questionnaire. Results. The majority (91%) of the ERRPs agreed that their work put them at risk of infection, but most (65%) did not agree that they should not be looking after patients infected with MERS. Despite that, 54% of ERRPs reported being afraid of contracting the infection from infected patients and only 4.2% of them were willing to change their current job. The majority of the ERRPs (85%) felt that their job would expose their families to risk of infection. Conclusions. Our study demonstrated the considerable psychological impact of MERS outbreaks on ERRPs. The ERRPs’ concerns and the psychological impact of MERS outbreaks should be considered in greater detail by hospital policymakers.